Associations of BAFF rs2893321 polymorphisms with myasthenia gravis susceptibility - Hui Deng; Jianjian Wang; Xiaotong Kong; Huixue Zhang; Tianfeng Wang; Wenqi Tian; Tingting Yi; Lihua Wang (BMC, 2019)
Abstract Background Myasthenia gravis (MG) is an autoimmune diseases characterized by fatigue and weakness of skeletal muscles. B-lymphocyte-activating factor (BAFF), an essential factor for B cell differentiation and development, is important in the progression of MG. The current study aimed to investigate the association between single nucleotide polymorphism rs2893321 in BAFF with MG susceptibility in Chinese Han population. Methods One hundred forty-nine patients with MG and 148 healthy controls were recruited. Using improved multiple ligase detection reaction technology, the polymorphisms of rs2893321 between groups and among MG subgroups have been compared. Results A significant differences between the MG group and the healthy control group was observed. Additionally, rs2893321 was found to be associated with gender and age in patients with MG. Conclusion Genetic variations of rs2893321 in BAFF might be associated with susceptibility to MG in the Chinese Han population.